Country-scale InSAR monitoring for settlement and uplift damage calculation in architectural heritage structures. (September 2021) - Drougkas, Anastasios; Verstrynge, Els; Van Balen, Koenraad; Shimoni, Michal; Croonenborghs, Thibauld; Hayen, Roald; Declercq, Pierre-Yves
The article proposes a methodology for assessing the development of damage in building structures, subjected to differential settlement and uplift, using the analysis of Interferometry Synthetic Aperture Radar (InSAR) data. The proposed methodology is targeted towards general applicability, capable of providing assessment results for measurements over wide geographic areas and for varying structural typologies. The methodology is not limited to ground movement measurements linked to tunnelling, as is the common case. Instead it extends to the monitoring of arbitrary movement in buildings, for example, due to ground consolidation, water table changes or excavation. The methodology is designed for use alongside patrimonial building databases, from which data on individual building geometry and typology are extracted on a region or country scale. Ground movement monitoring data are used for the calculation of the building deformation, expressed in different types of deformation parameters. The combined use of this data with analytical models for settlement damage classification in building structures enables the assessment in patrimonial building structures, at a country scale. The methodology is elaborated and applied on the patrimonial inventory of Belgium for the evaluation of potential settlement and uplift damage on buildings over a period of nearly three decades. The analysis results are compared to on-site observations.